Right at home : how good design is good for the mind - Berk, Bobby; Park, Jamie (Clarkson Potter/Publishers, 2023)
"Queer Eye's design expert presents an interior design guide that emphasizes self-care to help you find your own taste so you can optimize the function of every room and feel happier at home. The way your home makes you feel is one of the most important (and simplest fixes) that can affect your mental health. Your overall attitude both in and out of the home starts in the home, and hopefully with this book as a jumping off point. Gone are the days of designing homes just for showing them off to others. The functionality of a home has changed drastically with the onset of the pandemic and the massive increased time spent inside. Today, the home represents our ultimate safe space and needs to be able to host our most intimate conversations--so setting it up for comfort, style, and authenticity is essential to your self-care. In Right at Home, Bobby shows you how your home, no matter the size, can support your mental well-being and look good to boot. You'll learn how to: Articulate what makes you happy so you can design to reflect your truest style. Layer the lighting and enhance natural light so you feel (and look) your best. Know what to let go of and what to re-purpose so that every space is organized. Prioritize function and comfort for every room. Understand the impact of decor and confidently pick patterns, palettes, and pops. Right at Home shows us that changing the design of your space can aid mental wellness, and how we can achieve a new sense of happiness within the home. With highly visual home tours, Bobby's stories behind the designs (including Queer Eye fan favorites!), and gorgeous photographs of beautifully styled rooms, this is the definitive guide to designing your own home"--